Tingkat Literasi Informasi Mahasiswa Universitas Riau Berdasarkan Seven Pillars Model - Deliza Zakir; Sumarni; Nondot (Perpustakaan Universitas Riau, 2023)
The level of information literacy is a critical factor in this increasingly advanced digital era. Students as agents of change in society are required to have high information literacy skills in order to face the demands of a fast-paced and complex era. This study aims to analyze the information literacy level of Riau University students in the 2021-2022 period using the Seven Pillar Model. The method used is a quantitative descriptive method. The study population was 33,236 students, with a total sample of 395 respondents based on the Yamane formula. Sampling was done by accidental sampling technique. Data was collected using a questionnaire, which was distributed online and offline. Data processing and data analysis techniques use descriptive analysis. The results showed: 1) the mean score for the ability to understand information needs was 2.97. 2) the mean score of the ability to understand the type of information needed is 2.68. 3) the mean score of searching and accessing information skills is 2.70. 4) the mean score of the ability to search information is 2.79. 5) the average score of skills to compare and evaluate information 3.04. 6) the mean score of the ability to manage information, citing, writing ethics 2.50. and 7) the mean score of skills in compiling information products is 1.94. The conclusion of the research shows that students' ability in information literacy is in the high category.